Causal effect of differentiation strategy on organisational performance: the mediating effects of customer orientation and service innovation - Abdullah, Haim Hilman; Kaliappen, Narentheren (Inderscience Enterprises Ltd., 2016)
The purpose of this paper is to investigate the mediating effects of customer orientation and service innovation on causal link of differentiation strategy and organisational performance.Thus, an empirical study was conducted on 60 three- to five-star rated hotels in Malaysia to achieve the objective of this study.The findings show that differentiation strategy has a causal link on customer orientation and service innovation.Importantly, this study found that customer orientation and service innovation mediated the causal link of differentiation strategy and organisational performance.This is the first study that identifies mediating effects of customer orientation and service innovation on differentiation and performance nexus in Malaysian hotel industry.Finally, practical and theoretical implications are highlighted.